A Literature Review on Ergonomics, Ergonomics Practices, and Employee Performance - Koirala, Ranjana; Nepal, Ankit (Quest Journal of Management and Social Sciences, 2022)
Background: The modern history of ergonomics can be traced back to the world war from 1939 to 1945. From the 1960s to the 1990s, there were many changes made to ergonomics. Some of these were cognitive ergonomics, organizational ergonomics, positive ergonomics, and spiritual ergonomics. Ergonomics is becoming more of an issue in organizations in both developed and developing countries since the rise of occupational safety and health. Today, every company in the world puts more thought into making their workplaces safe. Objective: The goal of this study is to fill in the gaps in the evidence between ergonomics and employee well-being, focusing on ergonomics, ergonomic practices, and employee performance. Methods: This study uses an exploratory research design and gathers information from secondary sources to back up the title. Research papers are carefully chosen from scientific databases like Scopus, Web of Science, Science Direct, and Google Scholar by making criteria for each part to make sure the idea goes into depth and analyzes the role of ergonomics in improving employee performance. Results: Most research is done on physical ergonomics and organizational ergonomics. When people do research on ergonomics, they don't think much about how people act and think. Most ergonomics research is also done in industrial and developed countries, which makes sense. When it comes to research and use of ergonomics, developing countries are a long way behind. Most small businesses in developing countries don't care about ergonomics in the workplace. Conclusion: Accessing and improving ergonomics in the workplace could improve employee performance and productivity while reducing burnout, absenteeism, and turnover rates. So, it's important to study ergonomics more, especially for places like Nepal.